ChemInform Abstract: Copper(I) 2‐Hydroxyethoxide‐Promoted Cross‐Coupling of Aryl‐ and Alkenyldimethylsilanes with Organic Halides. Issue 15 (April 2015) - Takeda, Takeshi; Obata, Ryosuke; Muramatsu, Daisuke; Takeda, Yuichiro; Tsubouchi, Akira
Abstract: The reaction proceeds with retention of E/Z configuration of the substrates (VI), (VIII), and (X).